2012
DOI: 10.1016/j.juro.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A for Refractory Interstitial Cystitis/Bladder Pain Syndrome: Experience of 3 Tertiary Centers

Abstract: Cyclosporine A had a high success rate for patients with Hunner lesions in whom more conservative options, including endoscopic treatment, had failed. The success rate was low for patients without Hunner lesions. A 3 to 4-month trial is sufficient time to assess response. Adverse events were common and led to discontinuation of cyclosporine A for some patients. Close monitoring is needed, especially for blood pressure and renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…[95][96][97][98] Patients with Hunner's lesions seem to derive a better response than those without Hunner's lesions (68% vs. 30%, respectively). 96 A single RCT comparing CyA to PPS showed a significant improvement in IC/BPS symptoms with CyA treatment compared to PPS (59% vs. 13%, p<0.001). 99 This trial was not placebo-controlled and side effects occurred in 94% of CyA patients and 56% of PPS patients.…”
Section: Cyclosporine a (Cya) (Option As A Last Resort In Patients Wimentioning
confidence: 97%
“…[95][96][97][98] Patients with Hunner's lesions seem to derive a better response than those without Hunner's lesions (68% vs. 30%, respectively). 96 A single RCT comparing CyA to PPS showed a significant improvement in IC/BPS symptoms with CyA treatment compared to PPS (59% vs. 13%, p<0.001). 99 This trial was not placebo-controlled and side effects occurred in 94% of CyA patients and 56% of PPS patients.…”
Section: Cyclosporine a (Cya) (Option As A Last Resort In Patients Wimentioning
confidence: 97%
“…Eight articles (11)(12)(13)(14)(15)(16)(17)(18) were finally included as eligible articles, which including a total of 298 subjects with a median number of 37.25 subjects per study. These 8 studies included 3 RCTs (16)(17)(18), 4 prospective cohort studies (11)(12)(13)15) and 1 retrospective cohort study (14). In the 7 studies that reported the ages of the subjects, the age predilection was 40-70 years.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used the NIDDK criteria for diagnosing IC (12,14,(16)(17)(18); the other two studies used clinical symptoms to diagnose PBS/IC (11,13). The subjects of two studies (13,14) were patients in whom multiple first line therapies had failed.…”
Section: Resultsmentioning
confidence: 99%
“…Another randomized study of CyA efficacy found that CyA had higher clinical global response rates (75 %) than PPS (19 %) [61]. A recent multicenter retrospective review of ulcerative IC/BPS patients after failed intravesical therapies demonstrated an 85 % response to CyA therapy [62]. In contrast, only 30 % of patients without Hunner ulcers responded.…”
Section: Cyclosporinementioning
confidence: 99%